Species diversity and geographic mapping on non-volant mammals in Malagos Watershed, Mindanao, Philippines - Aloy, Alexander B. (2001)
This study aims to assess the non-volant mammalian species diversity and abundance at the Malagos Watershed locality and the geographic location identified species based on the several sites surveyed. Another objective is to describe the habitat conditions of the site through habitat analysis and correlate these to the abundance and species richness of non-volant mammals. A total of 11 non-volant mammals species belonging to 6 families and 6 orders were identified, of which Family Muridae had the most number of representative species. Murine rudents included species of the genus Rathus, Apomys, and Bullimus, which had similar body plans, relatively identical appearance. They differed in key external morphometrics such as tail, hindfoot, and total body lengths. Other conspicuous and easily identifiable species include the Cervus mariannus (Desmarest), Tarsius syrichta (Linnacus), and Paradoxurus hermaphroditus (Pallas). All of the Rathus species occurred and were trapped in almost all of the study sites with R. rattus (Temmick) and R. everetti(Gunther) emerging as the most abundant rodents. However, some species such as the Cynocephalus volans (Linnaeus) and the Viverra tangalunga (Gray) were found out to be threatened and declining in the locality. Diversity indices revealed higher diversity pattern within the less disturbed and well-vegetated forest interior and lower diversity in disturbed or agricultural sites. Furthermore, there was no profound linear relation between vegetation characters from Si to S5 (e.g. tree density) and diversity of mammal species
Thesis (BS Biology) -- University of the Philippines Mindanao, 2001